Sexual harassment in employment recent judicial and arbitral trends - Hodges, Jane Aeberhard (1996)
Abstract: Considers the issue of sexual harassment at work, aiming to identify which countries and which jurisdictions in those countries are advancing the law through the legal interpretation of related statutes, and demonstrating that sexual harassment at work is now attracting the law's full consideration. Sets out the legislative framework in which cases are filed and decisions taken in the regions under inspection ? North America, Europe, Asia and Pacific and Africa. Describes specific cases and arbitral awards since 1990 brought under labour laws, laws on non-discrimination, equality of opportunity, human rights, health and safety, civil and criminal law. Reaches a number of conclusions from the study: many jurisdictions are adopting the US approach that sexual harassment should be identified as a form of sexual discrimination; depending on the type of legal framework used, victims may obtain widely different results; the use of criminal law can be problematic because of the strictness of burden of proof; and the length of proceedings differs widely.